Aplikasi Visualisasi 3D Pada Struktur Sistem Rangka Manusia Berbasis Android - Satya Arisena Hendrawan; R. Rizal Isnanto; Ike Pertiwi Windasari (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2015)
The development of information technology has penetrated into various aspects of human life that it can perform an active role on information technology. In learning, for instance in the world of education, there are many simply interactive applications run on Android operating system . This application employs Unity 3D software as an editor. The initial step of making this final project is creating a design of user interface application. Waterfall Development used as methodology for developing this application. Stages of research method, requirements, design, implementation, testing, and maintenance. User application is capable to run all menus contained on the application of